Preventing Foodborne and Non-foodborne Illness: Vibrio vulnificus - Anita C. Wright; Renée M. Goodrich Schneider; Michael A. Hubbard; Keith R. Schneider (EDIS)
FSHN-09-02, a 3-page fact sheet by Anita C. Wright, Renée Goodrich Schneider, Michael A. Hubbard, and Keith R. Schneider, answers questions about this illness associated with eating raw oysters, describes how to receive and store seafood and shellfish, and explains how to prevent infection in high-risk individuals. Includes references. Published by the UF Department of Food Science and Human Nutrition, July 2009.